Adaptação às mudanças climáticas baseada em ecossistemas (AbE): análise da revitalização do córrego do Sapé (São Paulo) - Rolo, Daniella Aparecida de Mattos de Oliveira (2017)
The revitalization of urban rivers and streams plays an important role in the quest for environmental sustainability in cities. Notwithstanding the environmental degradation that affects their watercourses, cities are also suffering the impacts of another relevant process that deteriorates the environmental quality, climate change. To face climate change, in addition to mitigation measures, it is imperative to adopt adaptation measures. Green and blue infrastructure are solutions that reconcile engineering, plant restoration and water quality maintenance, which add ecosystem services to the revitalization of urban drainage, and may include ecosystem-based adaptation measures. In this context, the general objective of the research is the revitalization of urban streams in the promotion of measures to adapt to climate change based on ecosystems (EbA), from the case of the Sape stream. With this, we add the specific objectives in order to characterize the activities of the revitalization process of Sapé stream as a green and blue infrastructure; To identify the ecosystem services associated with the revitalization process of Sapé stream; To analyze the ecosystem services associated with the urban and environmental improvements promoted in the revitalization process in relation to measures of EbA and to evaluate if the EBAs meet the recommended in the Adaptation Plan to climate change in the Ministry of the Environment (MMA). This research has a qualitative and exploratory purpose. The sources of evidence for the accomplishment of the case study refer to: bibliographic research, documentary research, field data collection and semi-structured interviews. The results were obtained through documental, bibliographic analysis and interviews analyzed by the software IRAMUTEQ, after a comparison of the literature with the EbA found in the place. Finally, it is concluded that the recognition that urban drainage revitalization programs lead to EbA measures can contribute to a more in-depth discussion of the scope of public programs that aim to reverse the current degradation of urban rivers.